2013
DOI: 10.1093/aob/mct069
|View full text |Cite
|
Sign up to set email alerts
|

Root cortical burden influences drought tolerance in maize

Abstract: The results are consistent with the hypothesis that LCA is a driver of root metabolic costs and may therefore have adaptive significance for water acquisition in drying soil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
86
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(90 citation statements)
references
References 48 publications
(48 reference statements)
3
86
1
Order By: Relevance
“…Chimungu et al (2014) and Jaramillo et al (2013) reported that larger cells of the root cortical parenchyma reduce cellular respiration in this region, contributing to the deepening of the root system due to a lower metabolic cost, and that corn plants with lower cortex have higher drought tolerance, due to the smaller number of cell rows. Aerenchyma in corn roots may have the function of supporting a greater soil and water acquisition, since these structures decrease the metabolic cost of growing roots because of the reduced presence of cells in respiration (Zhu et al, 2010;Souza et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Chimungu et al (2014) and Jaramillo et al (2013) reported that larger cells of the root cortical parenchyma reduce cellular respiration in this region, contributing to the deepening of the root system due to a lower metabolic cost, and that corn plants with lower cortex have higher drought tolerance, due to the smaller number of cell rows. Aerenchyma in corn roots may have the function of supporting a greater soil and water acquisition, since these structures decrease the metabolic cost of growing roots because of the reduced presence of cells in respiration (Zhu et al, 2010;Souza et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Both RCS and RCA improve nutrient acquisition, driven by reduced root metabolic costs, and increase plant growth in edaphic stress (Zhu et al 2010;Postma and Lynch 2011a;Postma and Lynch 2011b;Schneider et al 2017b). However, reductions in nutrient and water transport and root respiration associated with RCS are significantly greater compared to RCA formation (Fan et al 2007;Zhu et al 2010;Postma and Lynch 2011b;Jaramillo et al 2013;Hu et al 2014;Saengwilai et al 2014;Chimungu et al 2015;Schneider et al 2017a).…”
Section: Rcs and Nutrient Remobilizationmentioning
confidence: 99%
“…Both RCS and RCA are accelerated by nutrient deficiencies (Gillespie and Deacon 1988;Drew et al 1989;Elliott et al 1993), reduce radial nutrient transport (Hu et al 2014;Schneider et al 2017a), reduce radial hydraulic conductivity (Fan et al 2007;Schneider et al 2017a), reduce metabolic costs (Zhu et al 2010;Postma and Lynch 2011b;Jaramillo et al 2013;Saengwilai et al 2014;Chimungu et al 2015), are influenced by exposure to ethylene (Lascaris and Deacon 1991b;Lenochová et al 2009;Schneider et al 2017c), and are types of PCD Jiang et al 2010;Schneider et al 2017c). Two ethylene-related genes were upregulated during both RCS and RCA formation (Rajhi et al 2011;Schneider et al 2017c).…”
Section: Rcs and Nutrient Remobilizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Under drought, maize genotypes with high RCA formation had greater root length, deeper rooting, better leaf water status, and 8 times greater yield than closely related genotypes with low RCA (Zhu et al, 2010a). Effects of RCA on root respiration were more pronounced for largediameter roots compared with small-diameter roots (Jaramillo et al, 2013). Results from the functionalstructural plant model SimRoot showed that RCA formation could be an adaptive response to deficiency of N, P, and potassium by decreasing the metabolic cost of soil exploration.…”
mentioning
confidence: 94%